2022
DOI: 10.1093/humrep/deac105.142
|View full text |Cite
|
Sign up to set email alerts
|

P-710 COVID-19 Vaccination and Infertility Treatment Outcomes

Abstract: Study question Is there an influence of mRNA COVID-19 vaccine on ovarian response and in vitro fertilization (IVF) treatment outcomes? Summary answer COVID-19 mRNA vaccine did not affect the ovarian response nor pregnancy rates in IVF treatment What is known already Studies demonstrated that infection with COVID-19 during pregnancy increased the risk of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Two studies provided median and interquartile range data. 38,40 Attempts to contact the authors to solicit the mean and SD from their study data were unsuccessful; therefore, the mean and SD were derived from the median and range using the formula developed by Wan et al 15 Two studies reported mean and 95% CI data 19,22 ; the SDs for these were derived using the method outlined by the Cochrane Handbook. 16 Seventeen studies reported data on our primary outcome (positive b-hCG and presence of a gestational sac on ultrasonography), with no significant differences between the vaccinated and unvaccinated patients across these studies (mean rate 52.6% and 57.2%, respectively), and an aggregated OR of 0.94 and 95% CI of 0.88-1.01 (P5.10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies provided median and interquartile range data. 38,40 Attempts to contact the authors to solicit the mean and SD from their study data were unsuccessful; therefore, the mean and SD were derived from the median and range using the formula developed by Wan et al 15 Two studies reported mean and 95% CI data 19,22 ; the SDs for these were derived using the method outlined by the Cochrane Handbook. 16 Seventeen studies reported data on our primary outcome (positive b-hCG and presence of a gestational sac on ultrasonography), with no significant differences between the vaccinated and unvaccinated patients across these studies (mean rate 52.6% and 57.2%, respectively), and an aggregated OR of 0.94 and 95% CI of 0.88-1.01 (P5.10).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 14 were conference abstracts and one was not available in English, leaving 25 original studies for inclusion in the final analysis. 19–43 A flow diagram representation of this methodology is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…We also analyzed data on whether COVID-19 vaccines affected the number of oocytes and MII/mature oocytes, blastocysts rate, and fertilization rate. Data on the number of oocytes from nine studies (18,19,22,(24)(25)(26)(27)(28)33) were combined, and the difference was not statistically significant (MD: 0.12; 95% CI: −0.65-0.88; P = 0.77; Figure 6). Moreover, there was no statistically significant difference in the number of MII/mature oocytes between the vaccinated and unvaccinated groups from seven studies (MD: 0.27; 95% CI: −0.36-0.90; P = 0.40; Figure 7) (18-20, 25, 26, 28, 33).…”
Section: Meta-analysismentioning
confidence: 97%
“…Quality assessment NOS quality assessment scored more than or equal to 7 as high quality, 5-6 as medium quality, and <5 as low quality (38). Overall, 19 of the 20 cohort studies (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(32)(33)(34)(35)(36)(37) were of high quality (NOS score ≥7). The remaining study (31) was of relatively poor quality, as summarized in Table 2.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The investigators did not find a difference in the oocyte fertilization rate and mean number of cryopreserved embryos at both cleavage and blastocyst stages. In addition, for those who underwent fresh embryo transfers, the clinical pregnancy rates were comparable between the vaccinated and unvaccinated participants (4).…”
mentioning
confidence: 91%